Social Skills and Medical Responsibility Across Development in Youth With Spina Bifida. (24th November 2020) - Stiles-Shields, Colleen; Shirkey, Kezia C; Winning, Adrien M; Smith, Zoe R; Wartman, Elicia; Holmbeck, Grayson N
Abstract: Objective : To examine the predictive role of social skills in youth with spina bifida (SB) on growth in medical responsibility across development. Methods : As part of a larger, longitudinal study, 140 youth with SB were assessed across four time points (ages 8–22 across time points). Mixed-effects models were investigated for change with: (a) no predictors (i.e., change in medical responsibility across age; time was examined using the participant's age, centered at 11.5 years); (b) social variables (i.e., observed social behaviors, parent- and teacher-reported social skills) as predictors; and (c) social variables as predictors with intelligence quotient, lesion level, and sex as covariates. Results : Significant growth with age was identified for medical responsibility ( p < .0001). Observed, parent-reported, and teacher-reported social skills did not significantly predict this growth; however, all three predicted the intercept for medical responsibility at 11.5 years of age ( p s ≤ .047). Parent-reported social skills remained a significant predictor of the intercept at 11.5 years of age when including the covariates ( p = .008). Conclusions : Children with SB who exhibited more positive social skills were more likely to a have higher level of medical responsibility in late childhood, but higher levels of social skills were not associated with a more rapid increase in responsibility over time. Identifying existing social strengths and promoting the practice of prosocial skills may have additional benefits to children with SB, including their acquisition of medical responsibility.